PENINGKATAN KINERJA GURU MELALUI PELATIHAN BESERTA FAKTOR PENENTUNYA - Slameto, Slameto (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2017)
The research aimed to evaluate the degree of teacher performance (in this case, teachers who are participating in â€œin-on model trainingâ€ and to find the encourage factors of teachersâ€™ (participants) performance. Two factors namely environment concern and their commitment to the school improvement were analyzed. This was a quantitative research method in which examines the causality among constructs in 30 respondents. The data were collected by using self-rating scale with 32 items grouped into four variables. Self-rating scale questionnaire was valid (0.314 â€“ 0.506) and reliable (0.632). The study found the level of teacher performance (training participants) with its encouraging factors. Most of them had high performance, leadership, middle social environment concern, and fairly good commitment. In addition, the research revealed that commitment among teachers improve 42.20% their work environment while teacherâ€™s leadership and social concern did not have significant influence toward teacher performance in in-on model training.